Thrombopoietin Activates Human Platelets and Induces Tyrosine Phosphorylation of p80/85 Cortactin - Fontenay-Roupie, Michaëla; Huret, Guillaume; Loza, Jean-Pierre; Adda, Raphaël; Melle, Josiane; Maclouf, Jacques; Dreyfus, François; Lévy-Toledano, Sylviane (Thrombosis and Haemostasis, 1998)
The mechanism of human platelet activation by thrombopoietin (TPO) was investigated in vitro. We found that rHuTPO stimulated thromboxane A2 formation and serotonin secretion, despite the absence of shape change and aggregation. Blockade of the arachidonic acid pathway did not inhibit rHuTPO-induced platelet secretion. rHuTPO stimulated the tyrosine phosphorylation of 64, 80/85, 95, 130 and 140 kDa proteins, but phosphoproteins of 100-105 and 125 kDa obtained when platelets aggregated in the presence of thrombin were absent. rHuTPO stimulated and potentiated the thrombin-induced tyrosine phosphorylation of a 80 kDa protein identified as the cortical actin-associated protein, p80/85 cortactin. When platelets were aggregated in the presence of rHuTPO and fibrinogen, cortactin phosphorylation was enhanced as compared to rHuTPO alone. Treatment with RGDS or cytochalasin D respectively reduced or abolished cortactin tyrosine phosphorylation. This confirms the existence of fibrinogen binding-dependent and independent pools of phosphorylated cortactin, both requiring intact actin polymerization. Cytoskeleton-binding proteins may be implicated in in vitro platelet activation by rHuTPO.